INTERPERSONAL COMMUNICATION OF TEACHERS AND BLIND CHILDREN IN INTRODUCING EARLY LITERACY IN SLB A YKAB SURAKARTA (BELIA: Early Childhood Education Papers, 2022)
This aim of this study is to explain how interpersonal communication of teachers and blind children in SLB A YKAB Surakarta in introducing early literacy, as well as factors that support and hinder interpersonal communication. This research is a descriptive qualitative case study research using observation method, interview and documentation methods in collecting data. Observations were made to observe the introduction of early literacy activities in the classroom, and then it continued with interviews with educators and parents. The collected documents serve as supporting data. Respondents used in this study were blind children, parents of students, class teachers and vice-principals in SLB A YKAB Surakarta. The technique used in data analysis is the theory of Miles and Huberman. The results of this study are about interpersonal communication of teachers and blind children in introducing early literacy. The introduction of early literacy in blind children teachers uses verbal, nonverbal, and paraverbal communication. Verbal communication used in the form of speech, singing and storytelling, nonverbal communication used through directives and hand movements, and paraverbal communication used through emphasis and intonation. Supporting factors in interpersonal communication to introduce early literacy to blind children are: (1) There is mutual trust (2) Openness (3) Comfortable environment. While the inhibiting factors are the condition of blind children, they are (1) The condition of students, the condition of students who are not only visually impaired becomes a teacher obstacle, the intended condition is the physical and psychological condition of the child. Keywords: Interpersonal Communication, Blind Children, Early Literacy, Supporting Factors, Inhibiting Factors